Efektivitas Tilang Elektronik atau Electronic Traffic Law Enforcement (ETLE) dalam Meningkatkan Disiplin Berlalu Lintas di Jakarta - Muhibbuddin, Muhammad; Sujono, Sujono; Sudarto, Sudarto (LITERATUS, 2025)
Ticketing for traffic violations on the highway using the Electronic Traffic Law Enforcement (ETLE) system. The existence of the E-ticket system makes it easier for people to pay fines through the bank. The implementation of ETLE is an effort to utilize Information Technology and Communication to support the process of road traffic law enforcement. For this reason, it will be further studied how effective electronic ticketing or electronic traffic law enforcement (ETLE) is in improving traffic discipline in Jakarta and how the factors that hinder the effectiveness of electronic ticketing or electronic traffic law enforcement (ETLE) in improving traffic discipline in Jakarta. The research method used in this study is the normative legal research method. From the results of the study, it was found that electronic ticketing or electronic traffic law enforcement (ETLE) is effective in improving traffic discipline in Jakarta, if law enforcement officers, in this case the Traffic Police, act as deterrents and enforcers for traffic violations that occur. The initiation of the application of the ETLE concept is actually in line with the direction of national legal development, especially in the direction of national legal development that focuses on efforts to eliminate and discipline traffic violations. There is no specific regulation that specifically regulates ETLE and the factors that hinder the effectiveness of electronic ticketing or electronic traffic law enforcement (ETLE) in improving traffic discipline in Jakarta is the regulation of the implementation of ETLE in PP 80/2012 has the potential to cause fundamental problems regarding the legal accountability of ETLE. PP 80/2012. The working mechanism of ETLE raises the possibility that traffic violators are not motor vehicle owners, while the Traffic Ticket will be sent with a database of motor vehicle owners in the motor vehicle registration and identification database. From the results of the study for improvement, it is expected that in terms of limited facilities and infrastructure that require a large budget, the Police can work together with local governments to provide facilities and infrastructure in enforcing ETLE and the government must form legislation, government regulations, and police chief regulations to provide justice, certainty and benefits for all parties related to the effectiveness of electronic traffic law enforcement (ETLE).